Sterol Biomarker Discovery In Neurodegenerative Diseases - MANUELA PACCIARINI (2023)
Neurodegenerative diseases (ND) are age-related heterogeneous disorders leading to uncontrollable neuroneal cell death. Nowadays, there is no cure or specific diagnostic biomarkers for ND. However, much evidence links disrupted brain cholesterol metabolism with the development of Alzheimer’s (AD) and Parkinson’s (PD) diseases, the two most common ND. Cholesterol is the most abundant sterol lipid in the human brain, the main component of myelin and a modulator of many neuroneal pivotal pathways. Several attempts have been made to understand the role and the entity of the sterol variations over PD and AD, highlighting modifications in the plasma and CSF content of the main brain cholesterol metabolite (24S)-hydroxycholesterol, (24S)-HC, and cholesterol itself but no conclusive results are yet reported. This thesis has been designed to study the plasma and CSF cholesterol and cholesterol metabolite variations in AD and PD, evaluating the ability of the discriminating sterols to be putative biomarkers. Our findings report a complete sterolome profile for AD CSF and PD plasma/CSF, identifying up to 21 different sterols. The results show an increase in the plasma levels of (24S)-HC and of 7α-hydroxy-3-ketone-cholestenoic acids in PD patients with respect to healthy controls. A decrease in plasma cholesterol is also observed in the PD group. However, (24S)-HC is the only sterol to also discriminate between males and females affected by PD and to demonstrate a diagnostic ability to predict PD. CSF and plasma sterols have also been screened in progressive PD, resulting in no significant variation, making them unsuitable prognostic biomarkers. In AD CSF, a positive correlation between the level of extracerebral 26-hydroxycholesterol, (24S)-HC and disease severity is reported. In conclusion, the results reported in this thesis support the use of cholesterol metabolites as diagnostic biomarkers for ND. However, validation studies on different cohorts of patients are needed.